Shielding innovation for health security: A PHITS-based optimization of Portland material for proton therapy - Damar Adhiwidya Suyanto; Aditya Tri Oktaviana; Mikael Syväjärvi; Yohannes Sardjono; Gede Sustresna Wijaya; Isman Mulyadi Triatmoko (FoundAE, 2025)
Proton therapy is an advanced treatment method for cancer that uses protons to irradiate tumors with high precision. However, the high energy of protons requires effective shielding to protect the surrounding environment and personnel from radiation exposure. In this research, the radiation shielding performance of Portland material was evaluated using the PHITS version 3.351 simulation software. The study focuses on assessing the attenuation of radiation within the cyclotron room under various operational conditions. The effectiveness of radiation shielding made from Portland material in a 230 MeV, 300 NA cyclotron room for a proton therapy facility was investigated. The results from PHITS simulations provide insights into the potential of Portland material in reducing radiation levels in proton therapy rooms, contributing to the safety and efficiency of such facilities. This analysis is essential for optimizing shielding design and ensuring compliance with safety regulations in proton therapy facilities.